Corredor de Memórias: Corpo, casa e objeto (Olhares, 2020)
Art and life are intertwined in the creation process of a stagecraft, which is presented as an analytical memorandum, developing intersections between references from the Performing Arts and Philosophy. A parallel is established between the house space and the scenic space, investigating the expressiveness of the body regarding specific aspects of the voice, sound, video and objects. It is intended to share certain aspects of the creation process, aiming to compose a plot of meanings that emerge from symbolic elements that mobilize the researcher and the research.
Keywords: Creative process; Body; Voice; Installation Art; Expressiveness